Reconfiguring gender, kinship, and spirituality: space- and place-making in Muslim Malaysia - Thimm, Viola (The journal of the Royal Anthropological Institute, 2025)
In the public and private spaces of Malaysia's capitalist cities, Malay women abide by a stricter Islamic dress code than they do in rural areas. Hence, in this local context, spatial public/private and ‘placial’ rural/urban order are of importance for gender identifications and practices. These orders imply influences on gendered forms of embodiment in the form of dress codes. This research examines the sociocultural constitutions of space and place in Malaysia regarding their relatedness to one another. The central argument states (1) that public space in Muslim contexts is defined as a social space in which men and women who are eligible to marry (non-mahram) encounter each other; and (2) that these relations are perceived and practised differently in urban and rural public and private spaces. This implies that the public-private divide is based significantly on gendered kinship relations: that is, concepts of family.
Veröffentlicht: 28 June 2024
Gesehen am 03.02.2025